Perancangan Tempat Penyimpanan Makanan dan Kebutuhan Kucing untuk Generasi Z di Lingkungan Urban - Candra, Hardian Purnama; Fajrin, Muhammad Alief Athallah; Yulardi, Audit; Maharany, Gunanda Tiara (Citradirga : Jurnal Desain Komunikasi Visual dan Intermedia, 2024)
This study presents a product—a storage container designed for cat food and essentials—tailored to meet the needs of generation Z who reside in apartments or rental homes and own cats. It addresses the prevailing issue of limited storage options for cat-related items, which often results in clutter and inefficient use of space. The primary objective of this product is to streamline storage and offer a designated area for feeding, thereby promoting organization and convenience. The design process entails gathering user feedback through surveys and creating user personas to gain insights into preferences and requirements. The outcome is a minimalist Japanese-style container characterized by efficiency and aesthetic appeal, featuring compartments for both food and essentials. This design enhances functionality while elevating the overall visual appeal of the living space.